2019
DOI: 10.1590/1678-9865201932e190050
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and cardiovascular risk in haemodialysis patients with chronic kidney disease

Abstract: Objective To verify the association between nutritional status and traditional and non-traditional cardiovascular risk factors in haemodialysis patients. Methods A cross-sectional study with 132 patients over 18 years of age on haemodialysis to evaluate nutritional status through Subjective Global Assessment. Information on traditional and non-traditional cardiovascular disease risk factors were obtained using a structured questionnaire; the Framingham score was also used to assess cardiovascular risk. Data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…Moreover, in this study, it was found that the cardiovascular risk scores were higher, and the majority of obesity indices were lower in the HD group than in the control, but ABSI and WHR were higher in women of the HD group. It has been shown in previous studies that the risk of cardiovascular disease is high in hemodialysis patients [35][36][37]. Risk factors such as renal dysfunction, duration of dialysis, uremic cardiomyopathy, oxidative stress, anemia, inflammation, and malnutrition may have resulted in a high risk of cardiovascular disease in the patients [36,38].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, in this study, it was found that the cardiovascular risk scores were higher, and the majority of obesity indices were lower in the HD group than in the control, but ABSI and WHR were higher in women of the HD group. It has been shown in previous studies that the risk of cardiovascular disease is high in hemodialysis patients [35][36][37]. Risk factors such as renal dysfunction, duration of dialysis, uremic cardiomyopathy, oxidative stress, anemia, inflammation, and malnutrition may have resulted in a high risk of cardiovascular disease in the patients [36,38].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown in previous studies that the risk of cardiovascular disease is high in hemodialysis patients [35][36][37]. Risk factors such as renal dysfunction, duration of dialysis, uremic cardiomyopathy, oxidative stress, anemia, inflammation, and malnutrition may have resulted in a high risk of cardiovascular disease in the patients [36,38]. Although most of the obesity indices were found to be low due to inadequate energy and nutrient intake in the patients, ABSI and WHR values were high in the HD group of women in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sendo importante ressaltar que ambas as patologias são consideradas fatores de risco cardiovascular (33).…”
Section: Métodosunclassified
“…Segundo a literatura a maioria dos pacientes submetidos ao tratamento de HD são homens, acima de 60 anos, com escolaridade menor do que 8 anos de estudos e baixa renda (33,10,35).…”
Section: Métodosunclassified